The evidence for and against different modes of tumour cell extravasation in the lung: diapedesis, capillary destruction, necroptosis, and endothelialization. Issue 4 (27th January 2017) - Paku, Sándor; Laszlo, Viktoria; Dezso, Katalin; Nagy, Peter; Hoda, Mir Alireza; Klepetko, Walter; Renyi‐Vamos, Ferenc; Timar, Jozsef; Reynolds, Andrew R; Dome, Balazs
Abstract: The development of lung metastasis is a significant negative prognostic factor for cancer patients. The extravasation phase of lung metastasis involves interactions of tumour cells with the pulmonary endothelium. These interactions may have broad biological and medical significance, with potential clinical implications ranging from the discovery of lung metastasis biomarkers to the identification of targets for intervention in preventing lung metastases. Because of the potential significance, the mechanisms of tumour cell extravasation require cautious, systematic studies. Here, we discuss the literature pertaining to the proposed mechanisms of extravasation and critically compare a recently proposed mechanism (tumour cell‐induced endothelial necroptosis) with the already described extravasation mechanisms in the lung. We also provide novel data that may help to explain the underlying physiological basis for endothelialization as a mechanism of tumour cell extravasation in the lung. Copyright © 2016 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.